CIVIC IDENTITY AND VALUES: SYSTEMIC VIEW - Fokina, Lyudmila (2023)
This article systematically analyzes the phenomenon of civic identity as a form of group identity. The nature of civic identity is considered within E. Erikson’s psychosocial approach. The terms and conclusions about the systemic nature of civic identity are based on the concepts of complex self-developing systems introduced by Academician V.S. Stepin. In such social systems, the basic and universal worldviews (values and meanings) act as the core program of self-regulation and reproduction. The content analysis of regulatory legal acts and policy documents has demonstrated that civic identity consists of universal and cultural values that are included in society’s cultural-genetic (civilizational) code. Based on the analysis of student essays on the topic "Values in my life", the authors assess the role of the family in the formation of values and propose to include interaction with students' families in the university educational process to form civic identity.